A review: production and postharvest management of Volvariella volvacea - M. J., Nur Sakinah; Misran, Azizah; Tengku Muda Mohamed, Mahmud; Abdullah, S. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Volvariella volvacea (Family: Plutaceae), also more commonly known as paddy straw mushroom, is an edible mushroom with high nutritional content. It is usually cultivated using lignocellulosic-based materials for enhanced production. However, V. volvacea is highly perishable and easily deteriorates in terms of quality and appearance after harvest. The present paper thus aimed to provide a critical review on aspects related to the production of V. volvacea using palm oil empty fruit bunch as cultivation substrate. The different stages of V. volvacea development are also highlighted. The present review also provides some information on the preservation techniques and appropriate postharvest management in extending V. volvacea shelf life to further boost the paddy straw mushroom industry.